2021
DOI: 10.3390/ijerph18105222
|View full text |Cite
|
Sign up to set email alerts
|

Positive Organizational Psychology: A Bibliometric Review and Science Mapping Analysis

Abstract: Positive organizational psychology (POP) is a research area that focuses on the positive aspects of optimal functioning at work. Although consolidated and with a large volume of publications, no bibliometric analysis has been performed that allows knowing its high-level structure, developments, and distribution of knowledge since its origins. The objective is to analyze the 7181 articles published in POP on the Web of Science Core Collection (WoSCC). A retrospective bibliometric analysis and science mapping we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Positive psychology emerged in the late 1990s to counterbalance the dominating psychopathological focus of the time (1). In the 22 years since its inception, positive psychology's strive to apply the scientific method to investigate the positive states, -traits, and -behaviors that enhance mental health, has spawned a magnitude of new theories, models and constructs (2,3). The growth of the discipline resulted in a rapid rise in the development and use of "positive psychological assessment measures" (PPAMs) aimed at measuring these positive psychological constructs validly and reliably (4).…”
Section: Introductionmentioning
confidence: 99%
“…Positive psychology emerged in the late 1990s to counterbalance the dominating psychopathological focus of the time (1). In the 22 years since its inception, positive psychology's strive to apply the scientific method to investigate the positive states, -traits, and -behaviors that enhance mental health, has spawned a magnitude of new theories, models and constructs (2,3). The growth of the discipline resulted in a rapid rise in the development and use of "positive psychological assessment measures" (PPAMs) aimed at measuring these positive psychological constructs validly and reliably (4).…”
Section: Introductionmentioning
confidence: 99%
“…Research in POP has shown exponential growth over the past 5 years ( Martín-del-Río et al, 2021 ). This exponential growth may indicate that the discipline is on the horizon of a new wave of research, innovation and ideas, which may fundamentally alter its discourse.…”
Section: Future Perspectives: Perma+4 and Pop 20mentioning
confidence: 99%
“…Positive psychology has emerged as one of the most rapid-growing sub-disciplines in psychology ( Martín-del-Río et al, 2021 ). During its first decade as a stand-alone science, positive psychological research has grown to account for 4% of all research conducted and published in psychology ( Rusk and Waters, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Science mapping has been widely used for studying the structure and development of various research fields such as visualization education research (Bratt, 2018), psychology (Flis & van Eck, 2018), integrative & complementary medicine (Moral-Muñoz et al, 2014), integrative and complementary oncology (Moral-Muñoz et al, 2019), information literacy (Stopar & Bartol, 2019), qualitative marketing research (Murgado-Armenteros et al, 2015), animal science research (Rodriguez-Ledesma et al, 2015), positive organizational psychology (Martín-Del-Río et al, 2021), female entrepreneurship studies (Deng et al, 2021), lean supply chain management (Garcia-Buendia et al, 2021), human resource management (Santana & Lopez-Cabrales, 2019), translation studies ( Wang et al, 2019), educational leadership and management (Gümüş et al, 2020; Hallinger, 2019, 2020; Kovačević & Hallinger, 2020), educational administration (Hallinger & Kovačević, 2019), sustainable entrepreneurship (Thananusak, 2019), sustainable tourism development (Yoopetch & Nimsai, 2019), and safety research and science (Jin et al, 2019; Li et al, 2021). In their study, Sajovic et al (2018) conducted a retrospective bibliometric analysis and mapping of the journal IEEE Transactions on Visualization and Computer Graphics , one of the leading journals in the field of VCG.…”
Section: Introductionmentioning
confidence: 99%